Solution of one task from game theory - Kirijackii, E. G. (Mathematical Modelling and Analysis, 1996)
“Решение одной задачи из теории игр”Mathematical Modelling Analysis, 1(1), p. 37-41.Article in Russian.First Published Online: 14 Oct 2010